ASSESSMENT OF STUDENT PERFORMANCE ON ONLINE LEARNING DURING PANDEMIC IN INDONESIA - Megawanti, Priarti; Wahyuni, Tri; Megawati, Erna (IJBLE Scientific Publications Community Inc., 2023)
The pandemic has had a negative impact in the form of learning loss. Learning loss during a pandemic was not only experienced by students but also by teachers. Some teachers have difficulty providing an objective assessment, especially psychomotor aspects. This quantitative descriptive research aims to determine teachers' constraints and solutions when assessing student performance. This research was conducted by distributing questionnaires in the form of Google Forms and distributing them to several teachers on Java and outside Java. Fifty-two teachers are willing to fill out the questionnaire completely. Based on the data processing results, it was found that one of the obstacles faced by teachers when giving assessments was the unfriendly internet network, the poor quality of videos or images sent by students, and confusion about who was doing the work (self-made or assisted by others). Some teachers think about and do ways to handle it. At the same time, some others allow the existence of competence that is not achieved.